Xanthophylls: potential benefits in protecting against UV burns - D. Q. Tavares; G. C. Santos; I. M. A. S. Mangussi; L. R. Vital; L. M. Nascimento; C. R. Oliveira (Brazilian Journal of Biology)
Abstract Exposure to ultraviolet (UV) radiation is a significant risk factor for sunburn (solar erythema) and skin cancer. Current treatments focus primarily on symptom relief, making the need for new therapeutic approaches urgent. Xanthophylls, a class of natural pigments with antioxidant and anti-inflammatory properties, show promise in the management of UV burns. This review aimed to systematically analyze the potential of xanthophylls for the management of UV burns, evaluating their efficacy in clinical and experimental studies. A literature review was performed following the PRISMA guidelines. Searches were conducted in the PUBMED, Virtual Health Library and EMBASE databases for eligible articles, using combinations of keywords such as astaxanthin, lutein, fucoxanthin and their effects on burns. Three independent reviewers conducted the search and selection of studies with inclusion criteria that addressed the use of xanthophylls in the treatment of burns, their mechanisms of action, pathophysiology and therapeutic approaches. Systematic reviews, letters, conference abstracts and case reports were excluded, considering only articles published in English. The articles were pre-selected by reading titles and abstracts, and the pre-selected studies were read in full for the final selection. Xanthophylls with potential benefits were identified, highlighting lutein, astaxanthin and violaxanthin, which demonstrated antioxidant activity by reducing the generation of reactive oxygen species (ROS) and mitigating inflammatory responses in skin cells exposed to UV radiation. Furthermore, evidence suggests that these xanthophylls promote skin barrier function and accelerate healing, enhancing recovery from UV burns. In conclusion, this review suggests a promising role for xanthophylls in alleviating UV burn symptoms and promoting skin healing. However, further research, including in vivo studies and clinical trials, is needed to validate its therapeutic potential, determine the optimal dosage, and optimize its delivery for effective UV burn control.